2022
DOI: 10.1101/2022.06.28.497936
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic regions insertion and deletion in Monkeypox virus causing multi-country outbreak-2022

Abstract: The genetic diversity and evolutionary origin of the Monkeypox virus (MPXV) that is currently creating a multi-country outbreak-2022 is not fully understood. Here we report that the MPXVs that cause outbreak-2022 (MPXVs-2022) have deletion/insertion of ~500 to 2000bp nucleotide in multiple genomic regions. Our analyses revealed that MPXVs-2022 are very close to the West African Clade of MPXVs (WA-MPXVs) that caused the Outbreak in Nigeria in 2017-2018. Furthermore, we classified the WA-MPXVs detected before 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Cases reported outside Africa, including those currently in circulation, have all been caused by the West African clade 9 , 13 . Whether genetic changes in the MPXV genome could be responsible for this current outbreak is currently being investigated 14 (see Box 2 for details).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases reported outside Africa, including those currently in circulation, have all been caused by the West African clade 9 , 13 . Whether genetic changes in the MPXV genome could be responsible for this current outbreak is currently being investigated 14 (see Box 2 for details).…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular epidemiology studies have shown a higher than expected rate of genomic variance among the outbreak sequences, suggesting accelerated evolution 242 and, potentially, APOBEC3 editing 244 . One preprint publication (not peer reviewed) reports the presence of insertions and deletions in the DNA of the MPXV strain that is circulating in the 2022 outbreak compared with MPXV strains that were circulating prior to 2017 and suggests that these changes may be responsible for the current outbreak 14 . However, it remains unclear whether and how these genetic differences drive the epidemiological phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Human monkeypox is a zoonotic infection caused by the monkeypox virus (MPXV) in Orthopoxvirus ( Adler et al, 2022 ) which contains a double-stranded DNA genome of ≈186–228 kb and encodes ~200 genes; however, MPXV has a genome size of ≈197 kb with nearly 190 genes ( Kugelman et al, 2014 ; Muhlemann et al, 2020 ; Desingu, 2022 ). The central ~100,000-nt region of the genome of this virus contains conserved genes required for virus transcription and replication, and its left and right arms contain genes that determine host innate immunity and host range ( Kugelman et al, 2014 ; Muhlemann et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…11 Surface glycoprotein B21R, a crucial antibody target, has three nonsynonymous single nucleotide polymorphisms (D209N, P722S, and M1741I) that may boost viral transmissibility. 9,11 In the form of genetic accordions [poxviruses can evade host antiviral responses by a series of gene activation and mutational processes], the vaccinia virus (VACV) is capable of developing mutations. The K3L gene has been amplified significantly in one strain of VACV, and this strain, along with a helpful point mutation in the same gene, allows the virus to effectively resist host PKR response.…”
Section: Genetic Diversity and Proteins Differences In Poxvirusesmentioning
confidence: 99%
“…At least 46 single‐nucleotide polymorphisms that are unique to this lineage exist 10 . For instance, the present outbreak may be caused by the MPXV strain that is circulating in the 2022 outbreak having more insertions and deletions in its DNA than the MPXV strains that were circulating before 2017 11 . Surface glycoprotein B21R, a crucial antibody target, has three nonsynonymous single nucleotide polymorphisms (D209N, P722S, and M1741I) that may boost viral transmissibility 9,11 …”
Section: Genetic Diversity and Proteins Differences In Poxvirusesmentioning
confidence: 99%